2020
DOI: 10.1101/2020.01.18.911388
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Construction, characterization, and immunization of nanoparticles that display a diverse array of influenza HA trimers

Abstract: Current influenza vaccines do not elicit broadly protective immune responses against multiple strains. New strategies to focus the humoral immune response to conserved regions on influenza antigens are therefore required for recognition by broadly neutralizing antibodies. It has been suggested that B cells with receptors that recognize conserved epitopes would be preferentially stimulated through avidity effects by mosaic particles presenting multiple forms of a variable antigen. We adapted SpyCatcher-based pl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…By using recombinant protein-based assays, this issue may be resolved, resulting in HI assay platforms that are easy to perform and standardize. Recently, a similar HA-nanoparticle design was used for immunization studies, and effective presentation of HA proteins was confirmed by electron microscopy (46). A comparable approach was also conducted for Middle East Respiratory Syndrome Coronavirus (MERS) serology, where the sialic acid binding MERS spike S1 A domain was presented on nanoparticles to perform HI assay (47).…”
Section: Discussionmentioning
confidence: 99%
“…By using recombinant protein-based assays, this issue may be resolved, resulting in HI assay platforms that are easy to perform and standardize. Recently, a similar HA-nanoparticle design was used for immunization studies, and effective presentation of HA proteins was confirmed by electron microscopy (46). A comparable approach was also conducted for Middle East Respiratory Syndrome Coronavirus (MERS) serology, where the sialic acid binding MERS spike S1 A domain was presented on nanoparticles to perform HI assay (47).…”
Section: Discussionmentioning
confidence: 99%
“…SpyCatcher003-mi3 particles were prepared by purification from BL21 (DE3)-RIPL E coli (Agilent) transformed with a pET28a SpyCatcher003-mi3 gene (including an N-terminal 6x-His tag) as described ( 54 ). Briefly, cell pellets from transformed bacterial were lysed with a cell disruptor in the presence of 2.0 mM PMSF (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…cytometry. B-cell analysis using flow cytometry was carried out as described(45). Briefly, single-cell suspensions were prepared from mouse spleens using mechanical dissociation, and red blood cells were removed using ACK lysing buffer (Gibco).…”
mentioning
confidence: 99%
“…We and others have recently evaluated nanoparticle immunogens that display multiple antigenic variants of viral glycoproteins as a potential route toward broadly protective vaccines (Boyoglu-Barnum et al, 2021;Cohen et al, 2021aCohen et al, , 2021bKanekiyo et al, 2019). Given the large number of coronaviruses circulating in zoonotic reservoirs, such vaccines could be important for understanding vaccine-induced neutralization/protection breadth and preventing future pandemics (Menachery et al, 2015(Menachery et al, , 2016.…”
Section: Design Assembly and Characterization Of Mosaic And Cocktail Sarbecovirus Rbd-npsmentioning
confidence: 99%